A Study on Stress Factors Influencing Conflict Management (International Journal of Scientific Research and Management (IJSRM), 2014)
Mental and physical health determines the individual’s life quality, productivity, work performance and activity. In addition, it also has a strong impact on the effectiveness and fruitfulness of the functions the individual has in his or her closer or wider environment and also influences his or her public and social activities. Based on this fact we can assert that the existence of programmes that maintain and support the health of the individuals – in other words the members of society – is a major social priority. The present study has collected responses from a convenience sample of 72 employees working in manufacturing units under different hierarchies through questionnaire method. The findings of the study are worth noting. The study found that the effectiveness of individual in conflict management aiming to preserve mental health is in close correlation with biological health protection and the optimal operation in dissolving conflicts, in which conflict manager has a major role.